2012
DOI: 10.3233/thc-2011-0648
|View full text |Cite
|
Sign up to set email alerts
|

A combination of Botulinum Toxin A therapy and Functional Electrical Stimulation in children with cerebral palsy – A pilot study

Abstract: Background: Among the ambulant population of children with spastic cerebral palsy (CP), dynamic equinus is one of the most common form of gait deviation that is encountered.Objective: To investigate the combined effects of Functional Electrical Stimulation (FES) and Botulinum Toxin A (BTXA) therapy in children with spastic CP, and to demonstrate the feasibility of this combination therapy.Methods: A single-subject design with repeated measures was adopted. Eight children (six males, two females; mean age 7 y 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The second most important advantage of the portable wireless device is its ease of use in a clinical environment. Although the wi-GAT is yet to be used in a clinical setting, the wired version of this device was successfully used to evaluate gait in a study on gait recovery in incomplete spinal cord injured subjects [12] and in an investigation of the combined effects of functional electrical stimulation and Botulinum toxin on walking in children with cerebral palsy [3]. The total duration to setup the portable wireless device and record the spatiotemporal gait parameters during a single trial is under 10 minutes, provided that insoles of various sizes are already instrumented and available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most important advantage of the portable wireless device is its ease of use in a clinical environment. Although the wi-GAT is yet to be used in a clinical setting, the wired version of this device was successfully used to evaluate gait in a study on gait recovery in incomplete spinal cord injured subjects [12] and in an investigation of the combined effects of functional electrical stimulation and Botulinum toxin on walking in children with cerebral palsy [3]. The total duration to setup the portable wireless device and record the spatiotemporal gait parameters during a single trial is under 10 minutes, provided that insoles of various sizes are already instrumented and available.…”
Section: Discussionmentioning
confidence: 99%
“…Gait analysis is a commonly used assessment tool that helps to quantify human locomotion. It has been widely used as a research and/or a clinical tool to quantify movement in various neurological conditions such as stroke [1,2], cerebral palsy [3,4], spinal cord injury [5], and also among the elderly population to assess the risk of falls [6].…”
Section: Introductionmentioning
confidence: 99%
“…Van Galen et al. reported a therapeutic increase in the angle of ankle dorsiflexion at the end of the swing phase and a trend of therapeutic improvement in foot contact pattern (without p ‐values for the latter parameter) . The increase in active ankle dorsal flexion in the post‐BoNT‐A phase was not as large as in the post‐FES and post‐control phases.…”
Section: Resultsmentioning
confidence: 99%
“…Five included articles with evidence at level IV 9,11,49,51,54 hint at causal inferences, while four level V studies 40,43,50,52 only suggest the possibility of causal inferences. On the basis of the five remaining articles, which are based on two group design studies of level II 10,39,41,42 and one singlesubject design study of level I, 46 it can be concluded that the outcomes are attributable to FES.…”
Section: What Is the Strength Of The Evidence?mentioning
confidence: 99%
“…It was observed that the activity of botulinum toxin, with functional electric stimulation as an adjunctive therapy, was very important to reduce the neurogenic component of spasticity and to increase calf inhibition and provide a mechanical stretching effect while strengthening the stimulate muscles [20]. Many case studies has been chosen to illustrate the combined effects of lower limb [21] FES or upper limb [22] FES and BTX-A therapy in children with spastic cerebral palsy, but in the absence of a control group in both trials. Recently, Tsuchiya M et al demonstrated for the first time the effect of combined use of BTX-A and FES in the treatment of spasticity in adults; they showed an improvement of active function in paretic hand [23].…”
Section: Introductionmentioning
confidence: 99%